THE IMPLEMENTATION OF PEER DICTATION TO TEACH LISTENING ANALYTICAL EXPOSITION TEXT TO ELEVENTH GRADE STUDENTS OF SMAN 1 KRIAN (RETAIN, 2016)
THE IMPLEMENTATION OF PEER DICTATION TO TEACH LISTENING ANALYTICAL EXPOSITION TEXT TO ELEVENTH GRADE STUDENTS OF SMAN 1 KRIAN Nita Andawati English Education, Faculty of Languages and Arts, State University of Surabaya nitaandawati@mhs.unesa.ac.id Drs. Fahri, M.A English Education, Faculty of Languages and Arts, State University of Surabaya fahri@unesa.ac.id Abstrak Dalam kegiatan mendengarkan bahasa inggris, masih ada kekosongan antara memenuhi kebutuhan siswa dan kebutuhan latihan mendengar. Terbatasnya ruang bagi siswa untuk belajar mendengar juga menjadi masalah yang dihadapi oleh siswa. Banyak cara yang dapat ditempuh oleh guru untuk mengatasi hal ini. Salah satunya adalah melalui teknik mendikte rekan. Penelitian ini bertujuan untuk menjabarkan bagaimana teknik mendikte rekan, salah satu variasi dari teknik mendikte, di implementasikan dalam membantu siswa di kegiatan mendengar, hasil dari pemahaman siswa dalam mendengarkan teks lisan, dan juga persepsi siswa terhadap penggunaan teknik mendikte teman. Penelitian ini dilakukan di SMAN 1 Krian. Peneliti mengamati kelas XI-Bahasa dimana teknik mendikte rekan di implementasikan. Teks yang digunakan dalam kegiatan ini adalah teks eksposisi analitis. Kuisioner diberikan untuk mengetahui pendapat siswa tentang teknik mendikte teman. Peneliti menggunakan desain penelitian kualitif dasar untuk mendapatkan data dan menjawab pertanyaan penelitian. Data dikumpulkan di dalam tiga pertemuan. Dari hasil penelitian, ditemukan bahwa guru mengadapatasi prosedur teknik mendikte rekan dari Jacob dan Small (1990) dan teknik ini di gunakan sebanyak dua kali. Hasil dari pemahaman siswa menunjukkan bahwa teknik mendikte rekan membantu siswa dalam memahami teks lisan. Hasil dari kuisioner menunjukkan bahwa kebanyakan siswa setuju bahwa teknik mendikte rekan membantu mereka dalam kegiatan mendengar. Kata Kunci: teknik peer dictation, mengajar mendengar, teks eksposisi analitis. Abstract In the listening activity, there is a gap between dealing with the learners’ need and the needs of the listening practice. Likewise, the limitation of listening activity in the classroom is being one of the obstacles that are faced by the students. To resolve this problem, there are many ways that teachers can do. One of them is by employing peer dictation technique. This study aims to describe how peer dictation is implemented to help the students in listening activity, the results’ of the students’ listening comprehension, and the students’ responses towards peer dictation. This research took place in SMAN 1 Krian. The researcher observed X1-Bahasa (Language program) where peer dictation was implemented. The text used was analytical exposition text. The questionnaires were administered to find out the students’ perceptions towards the implementation of peer dictation. Basic qualitative research was employed to collect the data and answer the research question. The data were obtained in three meetings. The findings show that the teacher adapted Jacob and Small’s (1990) procedure and peer dictation was implemented twice. The results of the students’ listening comprehension show that peer dictation helps the students to comprehend oral analytical exposition text. The results of the questionnaires reveal that most of the students agreed that peer dictation helps them in listening activity. Keywords: peer dictation technique, teaching listening, analytical exposition text.